Effects of asymmetry in Kondo channels on thermoelectric efficiency - Nguyen, T. K. T.; Cao, T. B.; Chu, T. A.; Nguyen, T. L. H.; Nguyen, H. Q.; Kiselev, M. N. (Communications in Physics, 2024)
We revisit an asymmetric two-channel charge Kondo model, which has been studied in the [Phys. Rev. B 82 (2010) 113306]. A nano-device modelling two-channel Kondo physics is a large metallic quantum dot which is embedded into a two-dimensional electron gas (2DEG) and connected strongly to two electrodes through two almost transparent single-mode quantum point contacts. The 2DEG is in the integer quantum Hall regime [Z. Iftikhar et al., Nature (London) 526 (2015) 233]. The reflection amplitudes at the quantum point contacts are asymmetric. We find that the thermopower and the figure of merit are decreased but the Kondo resonance width and Lorenz number in the vicinity of the Coulomb peak are lifted due to the effects of asymmetry in Kondo channels. We propose the method to improve the thermoelectric efficiency of the device.